Processing, microstructure and properties of Al0.6CoNiFeTi0.4 high entropy alloy with nanoscale twins - Chen, Weiping; Fu, Zhiqiang; Fang, Sicong; Wang, Yanping; Xiao, Huaqiang; Zhu, Dezhi (Materials science & engineering. A, Structural materials : properties, microstructure and processing, 2013)
Al0.6CoNiFeTi0.4 high entropy alloy was synthesized by mechanical alloying (MA) and spark plasma sintering (SPS). Only a FCC structure phase during MA was observed, while an ordered BCC phase and a FCC phase after SPS. The ordered BCC phase was much finer than the FCC phase after SPS. Moreover, twinning occurred only in the FCC phase during the SPS process. Al0.6CoNiFeTi0.4 high entropy alloy with a density of 98.2% and nanoscale twins exhibits excellent mechanical properties at room temperature. The yield stress, compressive strength and Vickers hardness of the alloy are 2732MPa, 3172MPa, 10.1% and 712±12HV, respectively. The fracture mechanism of this alloy is observed as intergranular fracture.